Stable 2D anti-ferromagnetically coupled fluorenyl radical dendrons - Wang, Jian; Kim, Gakhyun; Sandoval-Salinas, María Eugenia; Phan, Hoa; Gopalakrishna, Tullimilli Y.; Lu, Xuefeng; Casanova, David; Kim, Dongho; Wu, Jishan (Chemical science (Cambridge), 2018)
We report the first class of stable, two-dimensional (2D) anti-ferromagnetically coupled dendritic polyradicaloids. A kinetically blocked fluorenyl radical was used to build up the first and second generation dendrons FR-G1 and FR-G2 containing three and seven fluorenyl units, respectively. The neighboring fluorenyl radicals in FR-G1 and FR-G2 show moderate anti-ferromagnetic exchange interaction, resulting in a doublet and quartet ground state, respectively, with a small doublet–quartet energy gap. From FR-G1 to FR-G2 , the energy gap decreased and the two-photon absorption was enhanced owing to more extended 2D π-conjugation. Both compounds showed multiple redox waves due to their polyradical character.